Synergistic Effects of Nano –Zinc in Nano – Technology and Its Potential Influence on Bacterial Isolation from Women Experiencing Miscarriage - Hameed Abbas, Israa; Edan Kadhim, Rihab; Mohamed Al- Alwany, Shakir H. (Journal of Neonatal Surgery, 2025)
Background: The biological synthesis of zinc oxide nanoparticles (ZnONPs) using Juglans regia (walnut) bark extract presents an eco-friendly and sustainable alternative to conventional chemical methods. The phytochemicals present in the plant extract act as natural reducing and stabilizing agents, facilitating the conversion of zinc ions into nanoparticles. This green synthesis not only minimizes environmental impact but also enhances the biological properties of the produced nanoparticles. Aim of the Study: This study aimed to synthesize ZnONPs biologically using J. regia bark extract and evaluate their antibacterial activity against multidrug-resistant bacterial isolates (Klebsiella sp., Escherichia coli, and Enterobacter sp.) obtained from recurrent miscarriage (RM) cases. The study further investigated the potential use of these nanoparticles as a complementary treatment alongside antibiotics to overcome bacterial resistance. Materials and Methods: ZnONPs were synthesized by mixing the J. regia bark extract with a zinc precursor solution, where a color change from brown to light yellow indicated nanoparticle formation. UV-Visible spectrophotometry confirmed the synthesis with an absorption peak at 192 nm. Functional groups responsible for the reduction and stabilization were identified by Fourier Transform Infrared Spectroscopy (FTIR), showing the presence of carboxylic and polyphenolic compounds. X-ray Diffraction (XRD) analysis revealed the crystalline nature of the nanoparticles with an average size of 13.8 nm. Scanning Electron Microscopy (SEM) showed elongated aggregated nanoparticles with one end wider than the other. X-Ray Fluorescence (XRF) analysis revealed that the zinc content in the ZnONPs reached 16.72% compared to 0.51% in the raw bark extract. Antibacterial activity was tested against bacterial isolates from RM cases, with inhibition zones measured at concentrations of 25, 50, and 100 mg/mL, and the minimum inhibitory concentration (MIC) determined. Results: The biosynthesized ZnONPs showed strong antibacterial activity against the tested pathogens. The highest inhibition zones were recorded at all tested concentrations, with the MIC determined at 25 mg/mL. The antibacterial efficiency of ZnONPs was significantly enhanced by the phytochemicals in the J. regia bark extract, providing a potential alternative or complementary agent to conventional antibiotics against drug-resistant bacteria. Conclusion: The study demonstrates that J. regia bark extract can be successfully used for the green synthesis of ZnONPs with potent antibacterial properties. These nanoparticles show promising potential as alternative or supplementary agents in the treatment of infections caused by multidrug-resistant bacteria, particularly in recurrent miscarriage cases. Further studies are recommended to explore their synergistic effects with antibiotics and their safety profile in biological systems.